Normalization of B Cell Subsets but Not T Follicular Helper Phenotypes in Infants With Very Early Antiretroviral Treatment - Shalekoff, Sharon; Loubser, Shayne; Dias, Bianca Da Costa; Strehlau, Renate; Shiau, Stephanie; Wang, Shuang; He, Yun; Abrams, Elaine J.; Kuhn, Louise; Tiemessen, Caroline T. (Frontiers in Pediatrics, 2021)
Introduction: Infant HIV-1-infection is associated with high morbidity and mortality if antiretroviral treatment (ART) is not initiated promptly. We characterized development of circulating T follicular helper cells (cTfh) and their relationship to naïve/memory B cell subsets in a cohort of neonates initiating ART within the first week of life. Methods: Infants were diagnosed within 48 hours of birth and started ART as soon as possible. The frequency and phenotype of cTfh and B cells were analyzed at enrollment (birth - 19 days) and at 4, 12 and 72 weeks of age in blood of 27 HIV-1-intrauterine-infected and 25 HIV-1 exposed uninfected (HEU) infants as part of a study in Johannesburg, South Africa. cTfh cells were divided into Tfh1, Tfh2 and Tfh17 subsets. B cell phenotypes were defined as naïve, resting memory, activated memory and tissue-like memory cells. Results: HIV-1-infected infants had higher frequencies of cTfh cells than HEU infants up to 12 weeks of age and these cTfh cells were polarized towards the Tfh1 subset. Higher frequencies of Tfh1 and lower frequencies of Tfh2 and Tfh17 correlated with lower CD4+ T cell percentages. Lower frequencies of resting memory, with corresponding higher frequencies of activated memory B cells, were observed with HIV-1 infection. Importantly, dysregulations in B cell, but not cTfh cell, subsets were normalized by 72 weeks. Conclusion: Very early ART initiation in HIV-1-infected infants normalizes B cell subsets but does not fully normalize perturbations in cTfh cell subsets which remain Tfh1 polarized at 72 weeks. This altered cTfh phenotype may lead to impaired HIV-1-related and vaccine-related B cell responses despite ART and deserves further investigation.